Duration of night sleep and cognitive performance of community older adults - Élen dos Santos Alves; Sofia Cristina Iost Pavarini; Bruna Moretti Luchesi; Ana Carolina Ottaviani; Juliana de Fátima Zacarin Cardoso; Keika Inouye (Universidade de São Paulo, 2021)
Objective: to analyze the relationship between the duration of self-reported night sleep and the cognitive performance of older adults. Method: the sample consisted of 156 older adults registered in Family Health Units (FHUs) in a city of São Paulo, divided into quartiles according to the duration of night sleep. Data collection was performed using a characterization questionnaire, Addenbrooke's Cognitive Exam - Revised (ACE-R) and Pittsburgh Sleep Quality Index (PSQI). Descriptive, comparative and correlational statistical analyses were performed. Results: the older adults obtained a mean of 61.94 points in ACE-R and 55.1% presented good sleep quality. Comparative analyses showed differences between the groups only in the cognitive domain of verbal fluency (p=0.018). The post-hoc analyses showed that older adults who slept more hours, a mean of 8.85 hours (Q1), had lower scores when compared to those who slept a mean of 6.11 hours (Q3) (p=0.004) and of 4.52 hours (Q4) (p=0.045). The adjusted model with application of the stepwise method showed a relationship between the independent variables of schooling and sleep duration and the domain verbal fluency. Conclusion: it is concluded that sleep duration is related to the verbal fluency cognitive domain.